Learnt information in species-specific ‘trail pheromone’ communication in stingless bees - Reichle, Christian (2013)
Specificity in biological signalling systems is often important to keep information private. Foragers of several species of stingless bees deposit chemical marking signals to guide nestmates to food sources. The markings show species- and colony-specific compositions and primarily attract a bee’s nestmates. An interesting question is whether the bees innately recognize specific trail markings or learn their particular composition from nestmates. To investigate this question, we tested whether Scaptotrigona pectoralis and Scaptotrigona subobscuripennis workers taken from their mother colonies and workers that emerged from combs transferred to foster colonies of the congeneric species are attracted to the marking compounds of workers from their natal colony or from the foster colony. A significant majority of workers were attracted to extracts prepared from foragers of the nest they inhabited, regardless of whether this was the original mother or the congeneric foster colony. Thus, the preference of stingless bee workers for specific food-marking scent mixtures is not innate, but is influenced by the odour they experience within their colony. Despite marked differences in the chemical composition of the scent marks in labial gland secretions of the two investigated species they also shared some main components. We hypothesize that recruitment trail information in stingless bees is composed of one or a few key pheromone compounds acting in conjunction with an additional signature mixture that is species and colony specific and must be learnt by recruited workers.